Development of the Performance Characteristics of a Vertical Axis Wind Turbine (Global Journals of Research in Engineering, 2019)
- Performance curves aid in energy assessment and performance monitoring of wind turbines and can be used as a guide for turbine applications where a generic comparison between different types can be made before selection. This study design, build and carried out a performance analysis on a lift-type Vertical Axis Wind Turbine (VAWT). It was discovered that the efficiency of the wind turbine increased with tip speed ratios. A maximum tip speed ratio of 1.08 was achieved under limited wind speeds which meant that the rotational speed of the device was the same as the wind velocity.
Keywords: efficiency; drag-type; tip speed ratio; solidity